2017
DOI: 10.1093/mnras/stx2267
|View full text |Cite|
|
Sign up to set email alerts
|

The Herschel Bright Sources (HerBS): sample definition and SCUBA-2 observations

Abstract: We present the Herschel Bright Sources (HerBS) sample, a sample of bright, high-redshift Herschel sources detected in the 616.4 square degree H-ATLAS survey. The HerBS sample contains 209 galaxies, selected with a 500 µm flux density greater than 80 mJy and an estimated redshift greater than 2. The sample consists of a combination of HyLIRGs and lensed ULIRGs during the epoch of peak cosmic star formation. In this paper, we present SCUBA-2 observations at 850 µm of 189 galaxies of the HerBS sample, 152 of thes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
101
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(107 citation statements)
references
References 80 publications
(96 reference statements)
2
101
1
Order By: Relevance
“…Even with 10 missed lenses, the total number of lenses found on the SDSS is well below the number expected from the model (∼90 sources across the 121 sources with SDSS coverage; Bakx et al 2018). One obvious possibility, which we test in the next section, is that many of the lenses are too faint to be detected on the SDSS.…”
Section: Second Method: Recalculating the Reliabilitymentioning
confidence: 82%
See 4 more Smart Citations
“…Even with 10 missed lenses, the total number of lenses found on the SDSS is well below the number expected from the model (∼90 sources across the 121 sources with SDSS coverage; Bakx et al 2018). One obvious possibility, which we test in the next section, is that many of the lenses are too faint to be detected on the SDSS.…”
Section: Second Method: Recalculating the Reliabilitymentioning
confidence: 82%
“…We remove sources within 10 arcseconds of an NVSS source, which removes all bright blazar objects, and potentially some of the brightest non-blazar sub-mm sources. This survey is also able to find all blazar-objects in the early HerBS catalogue (Bakx et al 2018), and identified only three non-blazar sources.…”
Section: Extending the Lens-selection Methods On The Complete H-atlas mentioning
confidence: 98%
See 3 more Smart Citations